Digital Rehabilitation in Correctional Systems: A Case Study of Prospects and Barriers - Agalliu, Pjereta; Abrija, Admir; Karabegović, Isak (European Journal of Social Science Education and Research, 2026)
The integration of technology in correctional facilities represents a paradigm shift in modern prison rehabilitation approaches globally, offering unprecedented opportunities to enhance inmate reintegration while addressing systemic challenges. This research examines the global phenomenon of digital rehabilitation, using the current state and prospects of technology adoption in Albanian prisons as an illustrative case study. By analysing both opportunities for rehabilitation enhancement and implementation challenges, this study highlights the broader implications of digital tools in correctional settings. Through a comprehensive analysis of recent developments from 2020 to 2025, including international cooperation initiatives, this study reveals significant potential for digital transformation in correctional systems. Key findings indicate that technology-enhanced rehabilitation programs can reduce recidivism rates by up to 23% compared to traditional methods, while digital education platforms show 68% success rates versus 35% for conventional approaches. However, implementation faces substantial barriers globally, including high costs (85% impact), ageing infrastructure (78% impact), and staff training requirements (72% impact). The research demonstrates that strategic technology adoption, supported by international partnerships and phased implementation approaches, can transform prisons into modern rehabilitation-focused institutions. This study contributes to the growing body of international knowledge on correctional technology, providing insights that are transferable to other transitional contexts and informing global policy decisions.